Death bringer - Landy, Derek (London : HarperCollins Children's Books, 2012)
The Necromancers no longer need Valkyrie to be their Death Bringer, and that's a Good Thing.There's just one catch. There's a reason the Necromancers don't need her any more - because they've found their Death Bringer already, the person who will dissolve the doors between life and death.And that's a very, very Bad Thing...
4.8
5-8.
5-8
Keywords: Magic -- Juvenile fiction; Fantasy; Magic -- Fiction; Magic -- Fiction; Fantastic fiction; Fantastic fiction